Document template identification and data extraction using machine learning and deep learning approach - Roy, Kaushik; Islam, Md Fuad; Rimon, Md Minhazul Islam; Mobarak, Tasnim; Priota, Mysha Samiha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.